"I'm gonna teach them all the same way": teachers' beliefs about, experiences of, and classroom practices with children of color. Issue 1 (2nd January 2022) - Kintner-Duffy, Victoria L.; Scott-Little, Catherine; Smith, Nina
ABSTRACT: Children served in early care and education classrooms increasingly represent a variety of racial and cultural backgrounds. Such demographic changes have led to renewed attention to the importance of teachers' preparation and practices with children of color. Despite classroom demographics, early childhood teaching practices in the United States are informed by the dominant culture. Practices that do not respond to children's individual cultural identities may have negative effects on children's development, especially those children from marginalized cultures. This paper adds to the body of literature through semi-structured, qualitative interviews with 10 early childhood educators regarding their beliefs and practices with children of color and their experiences related to supporting racial and cultural diversity in the classroom. Results revealed limited knowledge and understanding of the role that culture plays in shaping child development and teaching practices. The lack of knowledge and minimal use of culturally responsive practices were largely influenced by teachers' personal experiences and limited exposure to the concepts of culture and cultural identities within their teacher preparation programs. Our findings emphasize the importance of improving the curriculum in higher education for early childhood care and education teachers. Recommendations for teacher educators are included.